A case study on the advertising techniques of Philippine Airlines in the international market after the February revolution - Arcenas, Fernando Antonio V. (Quezon City University of the Philippines Diliman, 1988)
This is a study of the kind of advertising techniques for the international market employed by Philippine Airlines advertisements before and after the Philippine Revolution of 1986.

The Source-Message-Channel-Receiver Communication Model of David Berlo in the book The Process of Communication: An Introduction to Theory and Practice, 1960, New York: Rhinehart and Winston, Inc., p. 40, is the basis of analysis of this study. This model or theory states that from the source comes whatever message is sent to the receiver or audience. The assumption here is that as the source changes, or as it changes its priorities (resulting, possibly, from external stimuli), the message may also change, and so may the attitude(s) of the receiver.

This study analyzed five different print advertisements found in international magazines, and interviewed two directors in Philippine Airlines' advertising and public relations department.

The study shows that the advertising thrust of Philippine Airlines indeed had changed, either directly or indirectly due to the Philipine Revolution of 1986. Prior to the Revolution, PAL's advertisements were of the hard-sell type, probably due to the unfavorable reputation the Philippines (and hence, Philippine Airlines) had under the Marcos Government. After the Revolution, a combination of the Filipinos' newfound popularity worldwide and the change of PAL's management shifted PAL's stance to a soft-shell one, focusing on the uniqueness, charisma, and beauty of the Filipino personality.
Thesis
Keywords: Advertising -- Airlines -- Philippines